Primary school pupils’ perceptions on narrative model essays in an ESL classroom / Jamuna Kanniappan - Jamuna , Kanniappan (2020)
Writing problems faced by Malaysian primary school pupils have led the teachers to find a way to help them in their writing ability. One of the strategies teachers have had is to use model essays in the writing classroom. This study examines the use of narrative model essays in a writing classroom in a school in Selangor. This study aims to identify the aspects of language which second language learners notice in reference to narrative model essays and gather insights regarding pupils’ perceptions on the use of narrative model essays in their narrative essay writing. The theoretical framework that underlines this study is ‘Output Hypothesis’. A case study was adopted to investigate how model essays have been used by primary school pupils in a writing classroom. A class of 22 pupils were selected and given a narrative writing task. Their first and second essays as well as annotated model essays were collected and analysed to identify the language aspects they noticed. In view of this, 6 pupils were randomly selected among the 22 pupils to be interviewed on their perspectives of using model essays in the writing classroom. Based on the pupils’ written essays and annotated model essays, it was found that the pupils noticed vocabulary the most followed by the other language aspects. In addition, pupils liked using model essays to guide them in their writing. The implications of the findings suggest that teachers can provide model essays prior to their written task and can have discussions in pairs or small groups to give pupils some guidance in their writing. Thus, model essays which serve as a feedback in the writing classroom can help the pupils to enhance their writing skills.